O ser no horizonte: imaginação transcendental em "Transposição", de Orides Fontela - Lucas Silvestre Cândido (2024)
Through the analysis of “Transposition”, a poem that opens the publication of the book of the same name (1969) written by the poet Orides Fontela, we seek to identify the theme poetically worked on in the text, based on what is said in it, to demonstrate how this theme conveys and is inserted in a certain discussion associated with the tradition of Modernity, according to the resources used by the author herself, characteristic of the time in which her poetics were founded. To this end, we made use of critics who focused on the historical and literary period to identify the movements to which we alluded, allowing us to find the context that ensured the parallel drawn between the poetics of Orides Fontela and his time, in this research aided by contributions of philosophical discourse. In the midst of this debate, we seek to raise the contradictions and implications that revolve around the dichotomy of subject and object, rationality and sensitivity, subjective and objective, poetry and philosophy, being and being, mediated by the singular figure of the image. Thus, the demands posed by the poem's text were readily associated with the criticism in vogue in high Modernism, with special attention to the 1960s generation, as well as finding support in Heidegger's philosophical proposition, based on fundamental ontology. What we conclude, then, is that the author, by manifesting certain knowledge in the inaugural poem, not only points to the direction that would guide her poetics, focusing on what specialized critics would note as the thematization of being to throughout his work, but it also establishes a dialogue between poetry and philosophy, exemplifying the possibility of this approach in Literature.